Factors influencing intention to use smart mobile apps Among local traveller in east coast - Muhammad Faiz Akif Fairus; Muhammad Faiz Fitri Abdul Rahim; Muhammad Fakhri Norazman; Muhammad Fakhruddin Che Khalid (2022)
The current study examined how social influence, performance expectancy, and price value influence intention to use mobile apps among east coast residents. This study focuses on the ease of use that leads to the intention to use smart mobile apps among consumers. Therefore, this research has used quantitative methods to achieve its objective. Researchers will examine 30 questions related to variables that have been established where all variables have a significant relationship with intention to use smart mobile apps among east coast residents using a "Google Form" or questionnaire. All of the information gleaned from this study will aid smart mobile app developers in creating apps that are simple to use for consumers, particularly those on the east coast. In conclusion, all the data in this study can be used as a reference for strategic planning in order to use smart mobile apps on the east coast and especially in Malaysia. Keywords: intention to use mobile apps, social influence, performance expectency price value.